PENGARUH TINGKAT KEPATUHAN WAJIB PAJAK DAN PEMERIKSAAN TERHADAP PENERIMAAN PAJAK PENGHASILAN - Olivia Jessica Yusuf Kastolani; Moh Didik Ardiyanto (Diponegoro Journal of Accounting, 2017)
The purpose of this study is to examine the influence the level of tax compliance and tax audit towards income tax revenue. Dependent variabel in this research is income tax revenue. Independent variabel used in this research is the level of tax compliance and tax audit.This research is categorized into quantitative approach using secondary data. This research population and also sample was individual tax payers and corporate tax payers listed seven KPP Pramata in Semarang City. Data were taken by year 2010-2016. Data were collected using several methods, including documentation and observation in the Directorate General of Taxation of Jawa Tengah I. Sampling method was proportional sampling. Data analysis was done by testing regression model with the classic assumption and continued by hypothesis testing. The test was using significance level 5%. The result of this study show that the level of tax compliance for individual tax payers was not significantly affects the income tax revenue but the level of tax compliance for corporate tax payers significantly related to income tax revenue, while tax audit for individual tax payers was significantly related to income tax revenue but tax audit compliance for corporate tax payers payers was not significantly affects the income tax revenue.